Natural variation in acyl editing is a determinant of seed storage oil composition. Issue 1 (December 2018) - Menard, Guillaume; Bryant, Fiona; Kelly, Amélie; Craddock, Christian; Lavagi, Irene; Hassani-Pak, Keywan; Kurup, Smita; Eastmond, Peter
Abstract Seeds exhibit wide variation in the fatty acid composition of their storage oil. However, the genetic basis of this variation is only partially understood. Here we have used a multi-parent advanced generation inter-cross (MAGIC) population to study the genetic control of fatty acid chain length inArabidopsis thaliana seed oil. We mapped four quantitative trait loci (QTL) for the quantity of the major very long chain fatty acid species 11-eicosenoic acid (20:1), using multiple QTL modelling. Surprisingly, the main-effect QTL does not coincide withFATTY ACID ELONGASE 1 and a parallel genome wide association study suggested thatLYSOPHOSPHATIDYLCHOLINE ACYLTRANSFERASE 2 (LPCAT2 ) is a candidate for this QTL. Regression analysis also suggested thatLPCAT2 expression and 20:1 content in seeds of the 19 MAGIC founder accessions are related. LPCAT is a key component of the Lands cycle; an acyl editing pathway that enables acyl-exchange between the acyl-Coenzyme A and phosphatidylcholine precursor pools used for microsomal fatty acid elongation and desaturation, respectively. We Mendelianised the main-effect QTL using biparental chromosome segment substitution lines and carried out complementation tests to show that a singlecis -acting polymorphism in theLPCAT2 promoter causes the variation in seed 20:1 content, by altering theLPCAT2 expression level and total LPCAT activity in developing siliques. Our work establishes that oilseed species exhibit natural variation in the enzymic capacity for acyl editing and this contributes to the genetic control of storage oil composition.